2019
DOI: 10.1007/s10899-019-09847-y
|View full text |Cite
|
Sign up to set email alerts
|

Level of Agreement Between Problem Gamblers’ and Collaterals’ Reports: A Bayesian Random-Effects Two-Part Model

Abstract: This study investigates the level of agreement between problem gamblers and their concerned significant others (CSOs) regarding the amount of money lost when gambling. Reported losses were analyzed from 266 participants (133 dyads) seeking treatment, which included different types of CSO–gambler dyads. The intraclass correlation coefficients (ICCs) concerning the money lost when gambling during the last 30 days were calculated based on the timeline followback. In order to model reports that were highly skewed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…The secondary outcomes were 1) gambling-related outcomes, as measured by the timeline follow-back (TLFB; Weinstock, Whelan, & Meyers, 2004) and treatment engagement. Studies have found that treatment-seeking gamblers and CSO are in fair agreement (ICCs just below 0.6) regarding the amount of self-reported losses using TLFB (Hodgins & Makarchuk, 2003; Magnusson, Nilsson, Andersson, Hellner, & Carlbring, 2019); 2) CSO’s depressive feelings, as measured by the Patient Health Questionnaire (PHQ-9; Kroenke, Spitzer, & Williams, 2001), anxiety, as measured by the Generalized Anxiety Disorder Scale (GAD-7; Spitzer, Kroenke, Williams, & Löwe, 2006), and quality of life, as measured by the 26-item version of the World Health Organization’s Quality of Life assessment (WHOQOL-BREF; Skevington, Lotfy, O’Connell, & the WHOQOL Group, 2004); and 3) relationship satisfaction, as measured by the relationship assessment scale (RAS; Rask et al, 2010). Measurements were administered at pretest and posttest and 3, 6, and 12 months after posttest.…”
Section: Methodsmentioning
confidence: 99%
“…The secondary outcomes were 1) gambling-related outcomes, as measured by the timeline follow-back (TLFB; Weinstock, Whelan, & Meyers, 2004) and treatment engagement. Studies have found that treatment-seeking gamblers and CSO are in fair agreement (ICCs just below 0.6) regarding the amount of self-reported losses using TLFB (Hodgins & Makarchuk, 2003; Magnusson, Nilsson, Andersson, Hellner, & Carlbring, 2019); 2) CSO’s depressive feelings, as measured by the Patient Health Questionnaire (PHQ-9; Kroenke, Spitzer, & Williams, 2001), anxiety, as measured by the Generalized Anxiety Disorder Scale (GAD-7; Spitzer, Kroenke, Williams, & Löwe, 2006), and quality of life, as measured by the 26-item version of the World Health Organization’s Quality of Life assessment (WHOQOL-BREF; Skevington, Lotfy, O’Connell, & the WHOQOL Group, 2004); and 3) relationship satisfaction, as measured by the relationship assessment scale (RAS; Rask et al, 2010). Measurements were administered at pretest and posttest and 3, 6, and 12 months after posttest.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the choice of distribution and link function can influence the ICCs calculated (Magnusson et al . 2019). We compared three possible distributional models (see Appendix S3): a gamma GLMM (with log link), a Gaussian model and a log‐normal model.…”
Section: Discussionmentioning
confidence: 99%
“…foraging ranges > 1000 km in Kittiwake, Guillemot and Razorbill), far beyond that which we observed and which could influence the reliability of calculated ICCs (Magnusson et al . 2019). Moreover, consideration of which distribution best reflects observed foraging ranges per trip is important because it can, in turn, be used to generate predicted foraging range radii for untracked colonies to help understand species space use using posterior distributions (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation